Identyfikacja obserwacji odstających w badaniach ankietowych z wykorzystaniem modeli regresji binarnych - Zdobylak, Joanna (The identification of outliers in survey research using binary regression models, 2006)
One of ihe most popular ways to get information about socio-economic occurrences is statistical research that uses questionnaires as a research tool. Within the analysis of this type of data the problem of outliers often appears. This article presents some of the methods of outliers identification. Those methods use binary regression. The author illustrates presented methods using an empirical example that shows advantages and disadvantages of those methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1105, s. 142-153